(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
This article analyzis that listening and listening comprehension (ECO) constitute a major pillar of the learning of the french as a second language (FLS), especially with allophone students in reception classes from Quebec. Their teaching through the implementation of teaching tasks likely to develop this skill in allophone learners in the classroom primary school reception is therefore an important element of linguistic integration and school of Allophone students. Given the lack of documentation regarding the teaching practices of ECO in the reception class, this research aims to describe the ECO tasks set up by the teachers in the reception classes of the primary and this, with a view to drawing up a portrait of it.